Speech and performance in Shakespeare's sonnets and plays - Schalkwyk, David (Cambridge University Press, 2002)
David Schalkwyk offers a sustained reading of Shakespeare's sonnets in relation to his plays. He argues that the language of the sonnets is primarily performative rather than descriptive. Schalkwyk provides a wide-ranging analysis of both the 1609 quarto of Shakespeare's sonnets and the Petrarchan discourses in a selection of plays.